Novel Interventional Approaches for ALI/ARDS: Cell-Based Gene Therapy - Ying-Gang Zhu; Jie-Ming Qu; Jing Zhang; Hong-Ni Jiang; Jin-Fu Xu (Mediators of Inflammation)
Acute lung injury (ALI) and its more severe form, acute respiratory distress syndrome (ARDS), continue to be a major cause of morbidity and mortality in critically ill patients. The present therapeutic strategies for ALI/ARDS including supportive care, pharmacological treatments, and ventilator support are still controversial. More scientists are focusing on therapies involving stem cells, which have self-renewing capabilities and differentiate into multiple cell lineages, and, genomics therapy which has the potential to upregulate expression of anti-inflammatory mediators. Recently, the combination of cell and gene therapy which has been demonstrated to provide additive benefit has opened up a new chapter in therapeutic strategy and provides a basis for the development of an innovative approach for the prevention and treatment of ALI/ARDS.